Investigations on the multistability of series-connected unsymmetric laminates - Kumar A.P.; Anilkumar P.M.; Haldar A.; Scheffler S.; Dorn O.; Rao B.N.; Rolfes R. (My University, 2025)
Multistable composite shells have received great attention in shape-changing morphing applications due to their ability to attain more than one stable shape when cooled down from curing to room temperature. However, an individual bistable shell may not completely fulfil all the requirements of a morphing structure as they may require more than two stable states during the morphing action. Also, on several occasions, cylindrical bistable shapes can be found to be limiting for morphing applications. Therefore, studies on highly multistable non-cylindrical shapes are a subject of interest. In this study, we explore how unsymmetric laminates connected in series can result in an increased number of stable shapes. To analyze series-connected laminates, a semi-analytical model is developed using the Rayleigh-Ritz approach. The shapes predicted by the semi-analytical model have been validated using the results from a full geometrically non-linear finite element model and corresponding experimental results. A further enhancement in the design space of series-connected laminates is proposed by replacing the conventional cross-ply laminate with curvilinear fiber variable stiffness (VS) laminates as they allow the designer to tailor stiffness properties. Although VS laminates can be used to generate the similar stable configurations as that of conventional cross-ply laminates, they may result in different curvature values leading to tailored snap-through requirements. The developed finite element model is extended to account for unsymmetric variable stiffness laminates, where effect of curvilinear fiber alignment on the multistable design space is investigated. © 2022 Elsevier Ltd